2011
DOI: 10.1039/c1sc00115a
|View full text |Cite
|
Sign up to set email alerts
|

Simple, robust molecular self-assembly on germanium

Abstract: We report the facile fabrication of high-quality, robust alkanethiolate self-assembled monolayers (SAMs) on germanium substrates. Our approach to produce SAMs on technologically important substrates takes advantage of the many strategies previously developed for gold-thiol self-assembly. Direct self-assembly of alkanethiols on germanium is impeded by the presence of the native germanium oxide. Using a mixture of water and ethanol, we create an environment where both adsorbate and oxide are sufficiently soluble… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
48
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 25 publications
(52 citation statements)
references
References 129 publications
4
48
0
Order By: Relevance
“…The intensity of C 1s (mixture solvent, 60 • C) > C 1s (mixture solvent, 25 • C) > C 1s (pure ethanol, 25 • C) > C 1s (pure ethanol, 60 • C) > C 1s (blank Ge). Based on the comparison of water contact angles and XPS spectra, it can be concluded that the mixture solvent system can suppress the degeneration/re-oxidation of NDM-passivated Ge and improve the coverage of NDM SAMs on Ge surface, and the moderate heating condition (60 • C) in mixture solvent system can improve the assembled coverage of NDM SAMs further [31]. The detailed temperature influence on NDM SAMs formation would be discussed in the following section.…”
Section: Solvent Influence On Sams Formationmentioning
confidence: 98%
See 4 more Smart Citations
“…The intensity of C 1s (mixture solvent, 60 • C) > C 1s (mixture solvent, 25 • C) > C 1s (pure ethanol, 25 • C) > C 1s (pure ethanol, 60 • C) > C 1s (blank Ge). Based on the comparison of water contact angles and XPS spectra, it can be concluded that the mixture solvent system can suppress the degeneration/re-oxidation of NDM-passivated Ge and improve the coverage of NDM SAMs on Ge surface, and the moderate heating condition (60 • C) in mixture solvent system can improve the assembled coverage of NDM SAMs further [31]. The detailed temperature influence on NDM SAMs formation would be discussed in the following section.…”
Section: Solvent Influence On Sams Formationmentioning
confidence: 98%
“…2 inset (b)), and the WCA was quickly increased to ∼101 • . In comparison to NDM quick assembly on Au (1 1 1) in seconds or minutes [34], the NDM SAMs formation process on Ge (1 1 1) was slower [29,31]. Following, the adsorbates were assembled in order with a slow reorganization process and the final WCA (Â Ge NDM ) reached a limit value ∼108 • (stable state, marked "c", Fig.…”
Section: Kinetics and Effectiveness Of Sams Formationmentioning
confidence: 99%
See 3 more Smart Citations